User acceptance model of computer-based assessment: moderating effect and intention-behavior effect - Lin, Jian-Wei; Lai, Yung-Cheng (Australasian Journal of Educational Technology, 2019)
Computer-based assessment (CBA) is an important area of e-learning research. Most studies of CBA technology add new constructs to existing user acceptance models and rarely consider the moderating effects and intention-behavior effects. Notably, within an e-learning environment, the self-regulation (SR) levels (i.e. high or low) substantially influence individual learning behavior and performance while intention-behavior effects are not guaranteed. This study investigates the moderating effects of SR levels on the relationships between the factors (including the intention-behavior relationship) of CBA acceptance model, which was based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The main findings are that, firstly, both the perceived performance expectancy and social influence significantly affect CBA behavioral intention in all students regardless of their SR level. Secondly, compared to effort expectancy in high-SR students, effort expectancy in low-SR students has a significantly larger effect on CBA behavioral intention. Finally, the behavioral intention significantly predicts CBA use behavior for the high-SR students but not for the low-SR students.